COMPLEX APPROACH TO DEVELOPMENT OF TECHNOLOGICAL EQUIPMENT FOR ELECTRO-IMPULSE POLISHING - I. V. Sinkevich (Наука и техника)
The paper contains results of the analysis pertaining to structures and regularities in shape-formation of electro-impulse polishing units that take into account a design, psychophysiology, ergonomics, functional painting and psycho-physiological perception of colour gamut.Design description of the electro-impulse polishing unit of «EPOL-6N»-series is given in the paper. The paper provides main technical characteristics of the unit and considers an application field of the given group of technological equipment.